2014
DOI: 10.1088/0268-1242/29/4/045021
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide thin films on silicon carbide substrates (ZnO/SiC): electro-optical properties and electrically active defects

Abstract: The electrical and optical properties of heterojunctions formed by thermally deposited ZnO thin films on n-type 4H-SiC substrates have been investigated. Current-voltage characteristics of the fabricated light emitting devices revealed excellent rectifying behaviors with a typical leakage current lower than 1 nA at a reverse bias of −3 V, and with a forward current at 3 V in the range of 2 mA. A study of the electroluminescent characteristics of ZnO/SiC heterojunctions over the temperature range of 50-450 K sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…As a result, rectification ratio, i.e., I on / I off (at 5 and −15 V, respectively) can be estimated at the level over 1 × 10 10 . Obtained values of electrical parameters are comparable or better than previously reported for n‐ZnO‐p‐4H‐SiC heterojunction diodes fabricated by different methods .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…As a result, rectification ratio, i.e., I on / I off (at 5 and −15 V, respectively) can be estimated at the level over 1 × 10 10 . Obtained values of electrical parameters are comparable or better than previously reported for n‐ZnO‐p‐4H‐SiC heterojunction diodes fabricated by different methods .…”
Section: Resultssupporting
confidence: 82%
“…However, 4H‐SiC seems to be quite interesting in this context as it is a wide band‐gap semiconductor applied in power devices, with lattice mismatch of about 5% with respect to ZnO, the same wurtzite crystalline structure, and excellent mechanical and chemical stability . Till date several reports on n‐ZnO/p‐4H‐SiC heterojunction diodes were published showing rectification ratios ( I on / Ioff ) about 1 × 10 5 , ideality factors 3–4 and leakage reverse current of the order of 1 × 10 7 A cm −2 . In spite of the significant progress in fabrication of ZnO‐based p–n heterojunctions, there still remains a problem of zinc oxide easy solubility during processing steps.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, although somewhat contradicting the energy band diagram suggested in ref. 20 , this might be the reason for the reported excellent rectifying characteristics of isotype ZnO/SiC heterojunctions 20 21 . The fact that just by choice of the deposition method it is possible to introduce a passivating zinc silicate – like dielectric layer with a large band gap at the ZnO/SiC interface might also be responsible for the reported high breakdown voltages and low leakage currents 21 .…”
Section: Resultsmentioning
confidence: 95%
“…It has been shown that SiC and ZnO can form high quality interfaces 17 promising this material combination to be applied in and beneficial for various optoelectronic devices, such as light emitting diodes, photodetectors, and solar cells. For instance, p-SiC/i-ZnO/n-ZnO heterojunction based diodes have shown random UV lasing 18 ; n-ZnO/p-6H–SiC heterojunction based diodes have demonstrated high photoresponsivity to UV light 19 ; n-ZnO/n-6H-SiC layer stacks show rectifying characteristics 20 ; for ZnO/n-4H-SiC heterojunctions rectification with high breakdown voltage and low leakage current is reported 21 ; and the photovoltaic power conversion efficiency of n-ZnO/n-SiC/p-Si heterojunction based solar cells is significantly higher than that of n-ZnO/p-Si based devices 22 .…”
mentioning
confidence: 99%
“…Engineering the interface between n-type ZnO and various material systems such as Si, GaN, and SrTiO 3 is proposed to improve the RS performance. For example, compared with n-ZnO/p-4H-SiC, Zhang et al showed that n-4H-SiC/n-ZnO heterojunction exhibits that the ON/OFF ratio increases from 10 8 to 10 10 . , Similarly, Li et al noted that in n-ZnO/i-MgO/n-GaN heterojunction, electrons and holes in the function layer can be restrained by the shallow traps and transfer to the n–n interface . Moreover, Zhou et al indicated that the ZnO/TiO 2 junction can affect the electron transfer efficiency owing to the conduction filaments formation and rupture, and the ZnO film may act as a blocking layer to protect from the permanent rupture …”
Section: Introductionmentioning
confidence: 99%